The relation of esophagogastroduodenoscopy time and novel upper gastrointestinal quality measures. Issue 7 (29th April 2022) - Romańczyk, Marcin; Romańczyk, Tomasz; Lesińska, Magdalena; Barański, Kamil; Hartleb, Marek; Waluga, Marek
Abstract : Objectives: Various measures of esophagogastroduodenoscopy (EGD) quality have been proposed so far and the examination time was one of the first. The aim of the study was to compare the procedure time with novel novel quality measures – composite detection rate (CDR) and endoscopist biopsy rate (EBR). Methods: It was prospective observational study. A total of 880 diagnostic EGDs conducted from 01.2019 to 07.2019 have been enrolled in the study. Results: Median EGD time was 4.2 min. Procedures of longer duration were marked with higher CDR (26.3% vs. 11.8%; P  < 0.0001), higher EBR (44.9% vs. 12.3%; P  < 0.0001), and better upper gastrointestinal neoplasm (UGN) detection (1.8% vs. 0%; P  = 0.004) in comparison with procedures of shorter duration. The procedures were divided into 4 groups based on the time quartiles (group 1 <3.3 min; group 2 3.3–4.2 min; group 3 4.2–5.3 min; group 4 >5.3 min). The odds ratios of groups 2, 3, and 4 for biopsy rate were 2.42 (95% CI, 1.33–4.55), 4.33 (95% CI, 2.46–7.94), and 5.51 (95% CI, 3.18–10.03), respectively, in comparison with group 1. The odds ratios of groups 2, 3, and 4 for CDR were 3.18 (95% CI, 2.03–4.97), 5.46 (95% CI, 3.51–8.50), and 23.44 (95% CI, 14.3–38.4), respectively, in comparison with group 1. Conclusions: The procedure time is related to novel metrics – CDR and EBR. It is also related to UGN. Based on our findings it could be concluded that EGD should not last less than 4.2 min.